IBI: Identification of Biomarker Genes in Individual Tumor Samples - Li, Jie; Wang, Dong; Wang, Yadong (Frontiers in Genetics, 2019)
Individual patient biomarker plays an important role in personalized treatment. Although various high-throughput sequencing technologies are widely used in biological experiments, high-throughput biological experiment is usually conducted once or few for a single patient, which makes it a challenging problem to identify biomarker of individual patient. At present, there is still a lack of effective methods to identify biomarker of individual sample data. Here, we proposed a novel method called IBI to identify biomarker of individual tumor sample. Experimental results on several tumor data sets showed that the proposed method can effectively find biomarker genes of individual patient, the common biomarkers which are related with the mechanism of development of cancer and can predict survival risk and drug response of different tumor patients. In summary, these results demonstrate that the proposed method offers a new perspective for analyzing individual sample.